PENEMPATAN PADA BANK INDONESIA DEPOSIT IN BANK INDONESIA DAN PENGARUHNYA PADA LABA BERSIH KEGIATAN USAHA BANK UMUM SYARIAH - Rully Trihantana; Abdul; Teguh Imanudin; Ika Santika; Naura Tanzilia Mumtazah (SAHID BANKING JOURNAL, 2022)
Sharia Bank business activities, one of which is the activity of placing funds at Bank Indonesia or the Central Bank, its function is to maintain excess liquidity in Islamic banks so that they can be channeled to Bank Indonesia, including SBIS FASBIS Demand Deposits and Others, contracts that usually used is a wadiah contract. In addition to maintaining the excess liquidity experienced by Islamic banks, placement of funds with Indonesian banks is carried out in order to maintain liquidity and also to fulfill BI's duties, namely by carrying out Islamic monetary operations. Against this background, the research question posed is whether and how placements with Bank Indonesia/Deposits in Bank Indonesia in terms of Current Accounts/Deposits, SBIS/Bank Indonesia Sharia Cerificates, FASBIS/Bank Indonesia Sharia Deposit Facilities, and Others/Other have an effect partially or simultaneously to Net Income? And what are the recommendations for contracts regarding placement with Bank Indonesia/Deposits in Bank Indonesia in terms of Current Accounts/Deposits, SBIS/Bank Indonesia Sharia Cerificates, FASBIS/Bank Indonesia Sharia Savings Facility, and increase a better effect on Net Profit. Whereas the variable X1 X2 X3 X4 has a significant effect on Y wake up seen from the results that are not that big because all the independent variables tested use wadiah contracts which are only savings contracts without profit sharing maybe in the future the contracts used can be more variously used by Bank Indonesia itself so that Islamic commercial banks do not feel too disadvantaged because they place their funds in Bank Indonesia rather than channeling them to the public.